ANALISIS VARIABEL YANG MEMPENGARUHI NIAT MENGADOPSI M-BANKING - ERNITA YUNAIRA (STIE Atma Bhakti, 2016)
The purpose of this study was to determine the variables that influence the adoption of m-banking customers of the Bank BRI Syariah Solo. The study also describes the relationship between the studied variables determine the effect perceived usefulness, perceived ease of use, relative advantage, customer awareness trust and attitude towards to adoption m-banking Bank BRI Syariah Solo with TAM (technology acceptance model) methods. Survey method chosen for data collection. The samples in this study were 173 customers who have the intention to adopt m-banking Bank BRI Syariah Solo. Purposive sampling was chosen to facilitate sample collection. Validity and reliability to ensure data quality. Statistical methods used are Structural equation model. The test results indicate that of the seven hypotheses were tested six hypotheses have significant among variables perceived usefulness to positively influence attitudes, perceived ease of use to positively influence attitudes, relative advantage affects positively the adoption of m-banking, trust positively affects the adoption of m-banking, trust positively affects the perceived usefulness and a positive attitude toward m-banking will lead to the intention to use m-banking. In this study, limitations and implications of the study are also described to provide guidance on the practical aspects, theoretical, and future studies. Key Word : perceived usefulness, perceived ease of use, relative advantage, customer awareness, trust, attitude toward, intention to adopt m-banking